3D Printing of Polyvinylidene Fluoride Based Piezoelectric Nanocomposites: An Overview. Issue 10 (12th June 2021) - Koroglu, Levent; Ayas, Erhan; Ay, Nuran
Abstract: Recently, polyvinylidene fluoride (PVDF) based nanocomposites have attracted much attention for next‐generation wearable applications such as promising piezoelectric energy harvesters (nanogenerators), energy storage devices, sensing devices, and biomedical devices due to their high flexibility, and high dielectric and piezoelectric properties. 3D printing technology, PVDF based piezoelectric nanocomposites, the studies based on 3D printing of PVDF based piezoelectric nanocomposites by inkjet printing and fused deposition modeling, and enhancements of energy harvesting and storage performance of nanocomposites by structural design are comprehensively overviewed here. An insight is provided into 3D printing techniques, structure and properties of PVDF based polymers, various nanofillers and production methods for nanocomposites, solutions to enhance β phase (crystallinity) of PVDF, and improvements of nanocomposites' breakdown strength, discharged energy density, and piezoelectric power output by mentoring structural design. Abstract : 3D printing technology, polyvinylidene fluoride (PVDF) based piezoelectric nanocomposites, and the studies based on 3D printing of PVDF based piezoelectric nanocomposites by inkjet printing and fused deposition modeling are comprehensively reviewed. Production methods, surface modification of nanofillers, and structural design significantly affect energy harvesting and storage performance of nanocomposites (elastic modulus, breakdown strength, discharged energy density, and power density).